Prevalence and correlates of low-level viremia and viral load non-suppression among adults on HIV treatment: Results from the Tanzania HIV Impact Survey, 2022–2023 - Samwel Sumba; Alexander Kailembo; Abbas Ismail; Prosper Njau; Alice Wang; Geofrey Mchau; Baraka Revocatus; Eliezer Anthony Taluka; Mary Mayige; Tepa Nkumbula; Faki Haji Faki; Optatus Malewo; et al. (PLoS ONE, 2026)
Background While HIV viral load (VL) testing remained a critical approach for monitoring antiretroviral therapy (ART) effectiveness among people living with HIV (PLHIV), limited national data existed on the magnitude and factors associated with key VL thresholds, including low-level viremia (LLV) and VL non-suppression in Tanzania. We analyzed the prevalence and socio-demographic and behavioral factors associated with LLV and VL non-suppression among PLHIV on ART participating in a nationally representative survey. Methods We analyzed data from the Tanzania HIV Impact Survey (THIS) 2022–2023 among PLHIV aged 15 years and older. The analysis included 1,485 PLHIV on ART with VL results. Laboratory-based testing was conducted for qualitative detection of antiretroviral (ARV) drugs and quantitative evaluation of VL. Three VL levels were computed for the analyses: undetectable VL (<50 copies/mL); LLV (50–999 copies/mL); and VL non-suppression (≥1000 copies/mL). Unweighted absolute numbers and weighted percentages were reported for descriptive analysis. We used modified Poisson regression models to examine separately the prevalence and factors associated with LLV and VL non-suppression. We reported adjusted prevalence ratios (aPR), 95% confidence intervals (CIs) and p-values <0.05 were considered statistically significant. Results Overall, 76% of PLHIV in Tanzania had undetectable VL, 18% had LLV, and 6% had VL non-suppression. Among PLHIV with either LLV or undetectable VL, 19.5% had LLV and after multivariable adjustment, absence of ARV drugs detected in blood was the only factor significantly associated with LLV. Additionally, among PLHIV with either VL non-suppression or undetectable VL, 7.2% had VL non-suppression and after multivariable adjustment, absence of ARV drugs detected in blood and alcohol use were associated with VL non-suppression. Conclusion In this nationally representative analysis of PLHIV in Tanzania, most people had undetectable viral load, while LLV was common and VL non-suppression was less frequent. Absence of ARV drugs detected in blood was associated with both LLV and VL non-suppression, underscoring the importance of recent ART exposure. These findings suggested that LLV warranted programmatic attention alongside VL non-suppression to support sustained viral suppression.